A hybrid actuator disc – Full rotor CFD methodology for modelling the effects of wind turbine wake interactions on performance. (August 2015) - Sturge, D.; Sobotta, D.; Howell, R.; While, A.; Lou, J.
Abstract: The performance of individual wind turbines is crucial for maximum energy yield, however, their performance is often reduced when turbines are placed together in an array. The wake produced by the rotors interacts with downstream turbines, resulting in a reduction in power output. In this paper, we demonstrate a new and faster modelling technique which combines actuator disc theory, modelled using wind tunnel validated Computational Fluid Dynamics (CFD), and integrated into full rotor CFD simulations. This novel hybrid of techniques results in the ability to analyse performance when simulating various array layouts more rapidly and accurately than using either method on its own. It is shown that there is a significant power reduction from a downstream turbine that is subjected to the wake of an upstream turbine, and that this is due to both a reduction in power in the wind and also due to changes in the aerodynamics. Analysis of static pressure along the blade showed that as a result of wake interactions, a large reduction in the suction peak along the leading edge reduced the lift generated by the rotor and so reduced the torque production and the ability for the blade to extract energy from the wind. Highlights: The actuator disc method for modelling the far wake of wind turbines is validated. A novel hybrid technique of actuator disc and full rotor CFD is developed. The new technique is used to model the effects of wake interactions on performance. The implications of wind turbine wake interactions are analysed and discussed. Wind turbines in the wake of another show a significant power reduction.